Clashing Voices : A study of gender and power dynamics in talk show interruptions - Laine, Jaana (My University, 2025)
This master’s thesis examines the gender differences in power dynamics in the context of talk show interruptions. While gender and interruptions have been a topic of research across various fields and contexts for the last 50 years, there is very little research on interruptions during talk show interviews. The aim of this study is to analyze what role gender and power-related aspects, such as status, play in the interruption behaviors of men and women. This study employs Feminist Critical Discourse Analysis by Lazar (2005), Conversation Analysis by Sacks, Schegloff, and Jefferson (1974), the Participant-oriented Approach by Köktürk and Özktürk (2012), and the categories of intrusive and co-operative interruptions by Murata (1994) and Li (2001). Six talk show hosts were chosen for this study, three of whom are men and three are women. They are Conan O’Brien, Larry King, and Jimmy Kimmel, as well as Ellen DeGeneres, Sherri Shepherd, and Kelly Clarkson. Two interviews were chosen from each talk show under special criteria, with one interviewee being a man and one a woman. The interviews were collected from the broadcasts’ verified YouTube channels. The study found that men interrupted 49 times, whereas women interrupted 40 times, with women more co-operatively. There was no notable difference in the occurrence of intrusive versus co operative interruptions by men. Men were interrupted by their interlocutor slightly more often, with no notable difference between the genders of the interrupters, whereas women were interrupted slightly more by men than by other women. The host interrupted 52 times, whereas the guest interrupted 37 times. Interviewers interrupted more co-operatively, whereas the guests interrupted more intrusively. Male hosts interrupted more than female hosts, and female guests interrupted more than male guests. In conclusion, gender played some role in the occurrence and number of interruptions, but the differences tended to be quite small. Instead of gender, contextual role (i.e., host versus guest) as well as social hierarchies (e.g., personal relationships, age differences) played a more prominent role in interruptions.
Keywords: critical discourse analysis, feminist critical discourse analysis, conversation analysis, participant-oriented approach, gender differences, interruption